"Environmental awareness" and rock climbing: changing pedagogies to enhance pro-environmental graduate attributes. Issue 2 (2nd April 2016) - Couper, Pauline; Porter, Su
Abstract: Geography has long been seen as having a central role in education for sustainable development, and yet the degree to which a geographical education translates to personal capacities for action has been questioned. Having struggled for some years to engage Outdoor Adventure Education students with physical geography science-based knowledge of the environment, we trialled a pedagogical shift to emphasize a relational, self-in-environment consciousness developed through autoethnography. We recount this experience to suggest that a similar approach may have potential to connect geography students' cognitive knowledge of societies and environments with personal identities and capacities for action.